(untitled) (Bangladesh Medical Journal Khulna, 2016)
Appendicitis is an extremely common presentation to general surgery in both adult and paediatric practice. Volvulus or torsion of the vermiform appendix, which is currently indistinguishable clinically from appendicitis, is an uncommon surgical emergency in children. Only a few cases are reported in the literature concerning this subject. We describe an 8 year old child who presented with right lower quadrant abdominal pain and was clinically diagnosed as perforated appendix. Laparotomy revealed a volvulus of the appendix and an emergency appendicectomy was performed. Bang Med J (Khulna) 2015; 48 : 32-33